Analisis Efektivitas Biaya Penggunaan Obat Antihipertensi pada Pasien Rawat Inap BPJS RSUD Prambanan Yogyakarta Tahun 2022 - Nurul Istiqomah; Kusumaningtyas S.A; Kharisma Jayak P (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Hypertension is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in two measurements with an interval of five minutes in a state of sufficient rest/calm. The aim of this study was to determine and compare the cost-effectiveness of antihypertensive drug combination therapy in BPJS inpatient hypertension patients at Prambanan Regional Hospital, Yogyakarta. This research was conducted non-experimentally using a descriptive research design of retrospective health phenomena based on a hospital perspective. The data used is secondary data (in the form of medical record data, financial data) and the research design used is cross-sectional. Inclusion criteria are hypertensive patients ≥18 years old with a primary diagnosis of stage II hypertension with or without comorbidities with BPJS payment. Cost effectiveness was carried out using the ACER and ICER methods. The results of the study showed that the most effective combination of antihypertensives was a combination of ACEI with diuretics. The direct medical costs for the combination of CCB and ACEI are IDR 1,229,906. The use of a combination of ACEI with diuretics is the most cost-effective with an ACER value of IDR. 14,313 and an ICER value of IDR. 10,070.